Formal-semantic paradigm of the word bash/bosh ‘head’, ‘beginning’ in turkic languages - Boris A. Musukov; Fatimat P. Erkenova (Кавказология, 2024)
The article is devoted to a multi-aspect study of the functional-semantic features of stock units of morphology of varying complexity, formed with the help of the polysemantic noun bash/bosh in various phonetic variants, known in Turkic languages ​​for its usage since ancient times, since the monuments of ancient Turkic writing.The work analyzes idioms of phraseological type, formed as a result of the loss of component meaning by free phrases. It examines elliptical shapes formed in the process of losing the word bash/bosh form 3 l. units h. The phonetic feature of the word bash/bosh in the Turkic languages ​​is that they all retain a single form, except for Uzbek.The article draws attention to the features of selective combination of syntactic constructions with the word bash/bosh with inventory units of morphology.